Ovulatory status and menstrual cycle duration assessed by self-collection of urine on pH strips in a population-based sample of French women not using hormonal contraception. (2nd November 2017) - Rosetta, Lyliane; Thalabard, Jean-Christophe; Tanniou, Julien; Ducot, Béatrice; Maitrot-Mantelet, Lorraine; Rousset-Jablonski, Christine; Bohet, Aline; Bouyer, Jean; Chimènes, Aline; Slama, Rémy
Abstract: Background: Assessing menstrual cycle function in the general population using a non-invasive method is challenging, both in non-industrialized and industrialized countries. Subjects and methods: The Observatory of Fecundity in France (Obseff) recruited on a nationwide basis a random sample of 943 women aged 18–44 years with unprotected intercourse. A sub-study was set up to assess the characteristics of a menstrual cycle by using a non-invasive method adapted to the general population. Voluntary women were sent a collection kit by the post and requested to collect urine samples on pH strips, together with daily recording of reproductive-related information during a full menstrual cycle. A total of 48 women collected urine every day, whereas 160 women collected urine every other day. Immunoassays were used to measure pregnanediol-3–α–glucuronide, estrone-3-glucuronide and creatinine. Ovulation occurrence and follicular phase duration were estimated using ovulation detection algorithms, compared to a gold standard consisting of three external experts in reproductive medicine. Results: Every other day urine collection gave consistent results in terms of ovulation detection with every day collection (intraclass coefficient of correlation, 0.84, 95% confidence interval, 0.76–0.98). The proportion of anovulatory menstrual cycles was 8%. The characteristics of the ovulatory cycles were length 28 (26–34), follicular phase 16 (12–23), luteal phase 13 (10–16) days median (10th–90th percentiles). Discussion-Conclusion: Assessing menstrual cycle characteristics based on urine sample spot only collected every other day in population-based studies through a non-invasive, well accepted and cost-limited procedure not requiring any direct contact with the survey team appears feasible and accurate.